Role of smoking and its impact on periodontium - Anshul Sawhney; Megha Ralli; Shishir Dhar; Bharat Gupta; Snehal Sunil Ghodke; Shamika Purao (Wolters Kluwer Medknow Publications, 2021)
Smoking is a major risk factor for increasing the prevalence and severity of periodontal destruction. Multiple cross-sectional and longitudinal studies have demonstrated that pocket depth, attachment loss, and alveolar bone loss are more prevalent and severe in patients who smoke as compared with nonsmokers. Smoking exerts a major effect on the protective elements of the immune response, resulting in an increase in the extent and severity of periodontal destruction. Several tobacco intervention approaches can be useful in helping the patient deal with the nicotine withdrawal symptoms and psychological factors associated with smoking cessation. In addition, pharmacotherapeutic treatments such as nicotine replacement therapy and sustained bupropion administration have proved effective.